UPAYA MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN PADA SISWA KELAS II MELALUI MEDIA FLASH CARD - Intan Permatasari; Didik Siswanto (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This study was conducted with the aim of improving early reading skills among second-grade elementary school students through the application of classroom action research. The issue identified in this study was the low level of early reading proficiency among second-grade students; specifically, 55% of the 20 students had not yet met the established minimum mastery criteria. The research process was carried out over two cycles, with each cycle consisting of two sessions; upon completion of all activities, a significant improvement in the students' early reading abilities was evident. This improvement was clearly demonstrated by comparing mastery percentages from the initial stage to the final stage. Initial observations showed that only eleven out of twenty students (55%) achieved the mastery score; this figure rose to thirteen students (65%) in the first cycle, and following the second cycle, the mastery rate surged by another 25 percentage points to reach 90% meaning nineteen out of twenty students had successfully met the early reading mastery standards. The study has demonstrated that the use of flashcards can significantly enhance early reading skills among elementary school students.